Socio cultural and agricultural local wisdom by cetho indigenous community to preserve the nature - Kadhung Prayoga; Adietya Muhammad Riezky; Aditya Rafi Syuhada; Dimas Setyo Prayoga (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
The green revolution has left a trail of civilization that is so awesome. Indonesia reached self-sufficiency in food through changes about ways of farming in the community. However, the development strategy which is the big push is gradually getting eliminates the values of local wisdom in farming activity. Farmers are directed in uniformity, from the use of the seeds, fertilizers, and pesticides. As a result, many local plant seed began to become extinct and replaced by new varieties that are sometimes incompatible with the environment. For this reason, this paper is present with the aim of seeing how the local wisdom plays a role in agricultural practices in the hamlet of Cetho, especially in terms of seedling onion. The approach used is a qualitative approach using descriptive method and the analysis of the discourse. The data used are the primary and secondary data collected through methods of the study of literature, interviews and observation. From the discussion it is known that in agricultural practices conducted by the people of Cetho hamlet is still full of local traditions that envelop. Local wisdom that exists not only related to the problem of solidarity among the people but has been rooted to the community activities in farming and its efforts to achieve environmental balance. One of them is in the manufacture and storage of onion seeds. The process, farmers choose seeds from the remaining good quality harvest, tied up and placed in a place that is in the kitchen ceiling. The goal is that the smoke from the fireplace can be about onion seeds so as to resist pest attack disease. This local wisdom has been obtained from generation to generation and practiced daily. However, it is necessary to study from the government or researchers related to onion seeds produced like this in the framework of the development of nature conservation based on local knowledge of the community.